The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1111/j.1945-5100.2003.tb00296.x
|View full text |Cite
|
Sign up to set email alerts
|

The Morávka meteorite fall: 4. Meteoroid dynamics and fragmentation in the atmosphere

Abstract: Abstract-Detailed analysis of the fragmentation of the Morávka meteoroid during the atmospheric entry is presented. The analysis is based on the measurement of trajectories and decelerations of fragments seen in a video and at the locations of energetic fragmentation events from seismic data obtained at several stations in the vicinity of the fireball trajectory. About 100 individual fragments are seen on video frames. Significant deceleration of the fireball at heights of ~45 km revealed that the meteoroid ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 20 publications
9
93
1
1
Order By: Relevance
“…Here ρ is atmospheric density and v is meteoroid velocity. Ordinary chondrites Morávka (Borovička & Kalenda 2003) (Borovička & Spurný 1996). However, applying the same destruction depth model as for Šumava, we found that the terminal flare would be expected at 55 km, if 2008 TC 3 were a low density (≈100 kg m −3 ) cometary body like Šumava.…”
Section: Discussionmentioning
confidence: 95%
“…Here ρ is atmospheric density and v is meteoroid velocity. Ordinary chondrites Morávka (Borovička & Kalenda 2003) (Borovička & Spurný 1996). However, applying the same destruction depth model as for Šumava, we found that the terminal flare would be expected at 55 km, if 2008 TC 3 were a low density (≈100 kg m −3 ) cometary body like Šumava.…”
Section: Discussionmentioning
confidence: 95%
“…Incoming meteoroids, on the other hand, easily fragment in the atmosphere under dynamic pressures two orders of magnitude smaller than the strength of meteorites (Petrovic 2001, Popova et al, in preparation). This is valid both for cmsized (Ceplecha et al 1993) and meter sized bodies Borovička & Kalenda 2003). The typical property of stony meteoroids is therefore presence of various internal cracks, which cause structural weakness of the body.…”
Section: Properties Of Stony Meteoroidsmentioning
confidence: 92%
“…This widely held belief was based on the observed fact that stony meteorites often hit the ground in showers of fragments (e.g. Jenniskens et al 1994), video-observed meteorite falls show extensive atmospheric fragmentation (Brown et al 1994;Borovička & Kalenda 2003), and detailed numerical modeling indicated that stony meteoroids always break-up in the atmosphere (Bland & Artiemeva 2006). In this paper, we discuss the Peruvian event in the context of data gathered from well-observed fireballs and perform simple modeling of the event.…”
Section: Introductionmentioning
confidence: 99%